Pengaruh Pelatihan Kerja dan Kompensasi terhadap Kinerja Agen Asuransi yang Tidak Memenuhi Target pada AJB BumiPutera 1912 Medan - Cici Hamidah; Ramadhan, Muhammad; Aslami, Nuri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the effect of job training and compensation on the performance of agents who do not meet target sat AJB BumiPutera 1912 Medan. This study aims to determine the effect of job training and compensation partially or simultaneously on the performance of agents who do not meet the target at AJB BumiPutera 1912 Mmedan. The method used in this research uses quantitative methods by taking 60 respondents from selected insurance agents as research samples through probability sampling tecniques with calculations using the slovin questionnaire formula using SPSS Version 25 testing and using linear data using multiple linear regression analysis methods. The results of this study simultaneuosly from job training variables (X1) and compensation (X2) have a positive and significant effect on the performance of insurance agents who do not meet the target and partially job training variables (X1) and job training (X2) also have a positive and significant effect on performance insurance agents who do not meet the target at AJB BumiPutera 1912 Medan. Keywords: compensation, insurance agents, job training,